Sex Determination from Dimensions of the Maxillary Sinus using Computerized Tomography - Aliu, Abdulhameed; Sirajo, Shiitu Bello; Usman, Jibrin; Bello, A. (IJRDO-Journal of Applied Science, 2018)
Background: Identification of corpses is a problematic forensic subject in cases of severe injuries, and exacerbated post mortem changes from mass burials and disasters with considerable skeletal remains. Identification of such human remains requires a comparison between ante-mortem and post-mortem evidences from intact, easily recoverable bones like the maxillae.Aim of the study: To determine the accuracy for gender determination by maxillary sinus dimensions.Materials and Methods:  130 subjects (79 males and 51 females), between  20 - 80 years, with normal maxillary sinus CT anatomy, from head CT scans carried out at the Radiology Department of the Usmanu Danfodiyo University Teaching Hospital (UDUTH) Sokoto were studied. The anteroposterior and transverse diameters were measured from axial images, while the craniocaudal diameter was measured from coronal and sagittal reformatted images. Using Neusoft Dual Slide Helical CT machine, measurements were taken between the widest points on the sinuses from three-dimensional reconstructed images using V-works 3.0 program.Results: The discriminant analysis showed that the left anteroposterior diameter accurately identified 73 subjects (56%) i.e. (42 males (53.2%) and 31 females (60.8%)), the left craniocaudal diameter accurately identified 55.4% of subjects i.e. 46 males (58.2%) and 26 females (51.0%).Conclusion: Computerized Tomography measurements of maxillary sinus dimensions may be helpful to support gender determination in forensic anthropology in addition to other methods of gender identification in unknown human specimen.